PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 002 BAGAN BATU KEC. BAGAN SINEMBAH - Dedi Afrizal; Damanhuri Daud; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Learning outcomes IPS SDN 002 Bagan Batu bagan Sinembah district low, there are still many students who have not reached KKM of 25 students only 10 people who completed (40.00%), while 15 people are not completed (60.00%) is due to students are less involved in the process of learning social studies, students are less motivated to learn IPS, students can not work together with a friend one group, so the learning outcomes to be low. This research aims to improve learning outcomes IPS Grade III SDN 002 bagan Batu bagan Sinembah district 2014/2015 academic year through "Cooperative Learning Model Application Examples Type Non Examples". This research was conducted in March 2015. The subjects were Grade III SDN 002 Chart Batu district. Chart Sinembah totaling 25 people. This research is a form of classroom action research consisting of 2 cycles. cycle each consist of two meetings. Data collection instruments in this study was the observation of student activity sheets and sheets of observations of teacher activity and test daily tests. The average value increased student learning outcomes in which the prior actions have increased at UH I 68.60 to 76.00 and rose again on the UH II became 86.00. Mastery learning students increased in the first cycle, the number of students who completed the 19 students with a percentage of 76.00% completeness then increased again in the second cycle, the number of students who completed 22 students with a percentage of 88.00% completeness. Activities of students and teachers also increased. Activity of students in the first cycle with an average of 69.44% categorized Enough, increased in the second cycle with an average of 88.89% categorized as good. Teacher activity also increased from the first cycle an average 70.83% with enough categories increased in the second cycle average of 87.50% with the good category. From the above shows that through the implementation of cooperative learning model examples of non examples it can improve learning outcomes IPS third grade students of SDN 002 Bagan Batu Sinembah district.Keyword : Cooperative learning model types Non Examples Examples, Learning Outcomes